HUBUNGAN KANDUNGAN ZINC DALAM AIR SUSU IBU DENGAN ZINC DARAh BAYI DI DAERAH PERKOTAAN, PEDESAAN DAN PANTAI - Joko Pambudi; Dewi Permaesih; Susilowati Herman (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 1999)
Association Between Zinc Level ol Breastmilk and Infant Blood in Three Different Areas.Zinc is an essential micro nutrient in many body metabolism. Breast feeding mothers should suffice their zinc consumption as their infants need zinc for maximum growth and development. The study aimed to look for a correlation between zinc level of breastmilk and of infant blood in three different areas. The sampels were 90 breast feeding mothers with their infants aged 4-6 months from three different areas: (i) urban, (ii) rural, and (iii) coastal. Information was gathered including food pattern and consumption, social economic, anthropometry, zinc level of breastmilk and infant blood. Breastmilk sample was collected in day time from the two nipples of mother, while blood sample was taken from arm vein of infant. This study found that zinc level in breastmilk differed in the three different areas. In urban area, zinc level of breastmilk was 0.91 ± 0.16 µg/ml, while in rural area was 0.75 ± 0.13 µg/ml, and in coastal area was 1.07 ± 0.40 µg/ml. Zinc level of breastmilk in urban area was siginificantly different to that in rural area (p<0.01), and zinc level of breastmilk for coastal area was significantly different to that in rural area (p<0.01). In respect to the level of infant blood, there were also differences. In urban area, zinc level of infant blood was 0.88 ± 0.17 µg/ml, while that in rural area was 0.66 ± 0.07 µg/ml, and in coastal area was 0. 73 ± 0.17 µg/ml. Infant blood zinc level in urban area was significantly different (p<0.05) compared to coastal area. However zinc level of infant blood for coastal area was not significantly different (p>0.05) from that in rural area. The study concluded zinc level of breastmilk in coastal area showed the highest, and zinc level in infant blood in urban area showed the highest. There was a strong correlation (r=0.5165, p<0.05) between breastmilk zinc level and infant blood zinc level only in rural area, but not in both urban and coastal area.Keywords: zinc level, breastmilk, infant blood, urban, rural and coastal.